2020
DOI: 10.5617/adno.8023
|View full text |Cite
|
Sign up to set email alerts
|

Digitalisering i grunnskolelærerutdanningen: Om faglige forskjeller i arbeidet med profesjonsfaglig digital kompetanse

Abstract: Forskning viser at utviklingen av lærerstudenters profesjonsfaglige digitale kompetanse (PfDK) i svak grad har vært arbeidet med i norsk grunnskolelærerutdanning. Imidlertid er det behov for oppdaterte studier og kunnskap om hvordan ulike fag i dag arbeider med PfDK. I artikkelen har vi lagt Rammeverk for lærerens profesjonsfaglige digitale kompetanse (lansert av Utdanningsdirektoratet i 2017) til grunn når vi har innhentet og analysert data. Vi undersøker om det er forskjell mellom hvordan lærerutdannere fra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…However, they were also aware of the differences between the digital competence that teachers need and that required by other professions, and that the acquisition of knowledge within the PDC framework requires different approaches. Students' stories from this study support previous research that has concluded that TE is better at using digital technology than it is working with topics that are relevant in the digital age (Hjukse et al 2020, Tømte et al, 2013Gudmundsdottir & Hatlevik, 2018).…”
Section: Pdc 'In the Making'supporting
confidence: 80%
See 1 more Smart Citation
“…However, they were also aware of the differences between the digital competence that teachers need and that required by other professions, and that the acquisition of knowledge within the PDC framework requires different approaches. Students' stories from this study support previous research that has concluded that TE is better at using digital technology than it is working with topics that are relevant in the digital age (Hjukse et al 2020, Tømte et al, 2013Gudmundsdottir & Hatlevik, 2018).…”
Section: Pdc 'In the Making'supporting
confidence: 80%
“…They also revealed that students were aware of the risks of finding inappropriate content online but that they had only limited competence in dealing with privacy and copyright issues (Gudmundsdottir & Hatlevik, 2020). Hjukse et al (2020) indicated that PDC development varied from subject to subject, and that teacher educators tended, in general, to focus more on how digital technology should be applied in education, rather than addressing the various issues that users encounter in digital educational contexts, such as digital bullying and adapted learning (Hjukse et.al., 2020). Lund and Aagaard (2020) have questioned the idea that TE, in its efforts to foster student teachers' PDC, tends to focus too much on the use of digital technologies at the expense of addressing deeper and more epistemological issues.…”
Section: What Do We Know About Pdc Development In Teacher Education?mentioning
confidence: 99%
“…Furthermore, previous studies over the past five years only measured the significance of teacher education (TE) in enhancing teachers' professional digital competencies. These studies have employed both quantitative [35][36][37] and qualitative approaches [38][39][40][41][42]. In addition, multiple studies have also shown that the technology leadership practices of principals play a crucial role in improving the skills and effectiveness of teachers when it comes to integrating technology into the learning process [18,[43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Digital competencies and skills are embedded into the national curricula for compulsory education, there are national strategies and action plans for digitalisation, and the digital states of schools is monitored nationally (Erstad et al, 2021). Moreover, funding has been earmarked for monitoring the digital transformation of schools and for teacher training initiatives (Olofsson et al, 2015;Hjukse et al, 2020). In Norway, school districts own the schools that offer compulsory education.…”
Section: Introductionmentioning
confidence: 99%